Effect of Pulse Widths and Cycles on Invasive, Bipolar, and Gated Radiofrequency-Induced Thermal Reactions in ex vivo Bovine Liver Tissue - Choi M; Lee HS; Cho SB (Dove Medical Press, 2023)
Min Choi,1 Hye Sun Lee,2 Sung Bin Cho3 1R&D Center, Shenb Co., Ltd, Seoul, Korea; 2Department of Biostatistics, Yonsei University College of Medicine, Seoul, Korea; 3Yonsei Seran Dermatology and Laser Clinic, Seoul, KoreaCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, Geumcheon REMAIN CITY 6F, 224 Siheung-daero, Geumcheon-gu, Seoul, 08628, Korea, Tel +82.2-2135-1375, Fax +82.70-8250-1375, Email drsbcho@gmail.comBackground: Radiofrequency (RF) oscillations generate thermal tissue reactions, the patterns of which vary depending on the mode and efficiency of energy delivery. The aim of our study was to analyze patterns of RF-induced thermal tissue reactions according to the modes of RF delivery, including continuous and gated modes, using an alternating current, invasive bipolar RF device.Methods: RF energies at frequencies of 1 and 2 MHz were delivered at respective experimental settings into ex vivo bovine liver tissue at a 0.5-mm microneedle penetration depth. The tissue samples were then evaluated thermometrically. A histologic study was performed to evaluate RF-induced thermal tissue reactions at a 3.0-mm microneedle penetration depth.Results: Thermal imaging study revealed homogenous, well-demarcated, square-shaped zones of RF-induced thermal reactivity on the treated area. Multivariate linear regression analysis revealed that higher temperature elevations immediately after RF treatment (∆T1) were positively associated with RF frequency, power, conduction time/pulse pack, and off-time between pulse packs and negatively associated with total off time. In the 1-MHz experimental setting, higher ∆T1 showed a positive association with power, conduction time/pulse pack, and off-time between pulse packs and a negative association with the number of pulse packs. In the 2-MHz setting, however, higher ∆T1 was positively associated with only total treatment time.Conclusion: Thermometric effects during bipolar and gated RF treatments are significantly associated with the frequency, power, and pulse widths and cycles of pulse packs.Keywords: radiofrequency, bipolar, alternating current, gated pulse, tissue reaction, bovine liver